THE EARLY ARAGONESE PARDINA : ITS ETYMOLOGY AND FUNCTION - Nelson , Dr. Lynn H. (مجلة كلية الاداب, 1975)
The majority of the population of Upper Aragon has tra Jelly tended 10 group itself in nucleated communities, but aus isolated habitations dot hte landscape. There are us types of such establishments, serving different funct e and called by distinctive names. Pajares and bordas are Celatively modest dwellings serving the temporary needs of the chepherds of the region, while the casetas act as field quarters during the height of the agricultural season